The Effect Partnership on Performance Small and Medium Enterprises based Law No.9 of 1995 in Tebing Tinggi City - Hulu, Fonaha (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study examines the effect of partnership on the performance of small and medium businesses in Tebing Tinggi City. the research method description analysis using a qualitative research approach, data collection through interviews and literature. Based on law number 9 of 1995 article 1 paragraph 8 "Partnership is a business collaboration between small businesses and medium businesses or large businesses accompanied by coaching and development by medium businesses or large businesses by paying attention to the principles of mutual need, mutual need, mutual strengthening and mutual benefit". This economic group of small and medium businesses is one of the businesses that has proven to be surviving in the midst of the development of the terrible economic crisis that has hit the country. Partnerships are very important in developing small and medium businesses because the existence of small and medium business partnerships is facilitated to obtain capital and marketing systems. In an increasing competitive atmosphere, the existence of small and medium businesses is demanded to remain able to compete with other business actors, because this institution is considered to be quite representative in empowering the community's economy.